Dual effects of climate change and socioeconomic development on flood exposure in the Yellow River Basin, China - Yixin Sun; Qiang Zhang; Gang Wang; Chong-Yu Xu; Vijay P. Singh; Da Liu; Kaiwen Zhang; Anlan Feng; Hushuang Ma (Journal of Hydrology: Regional Studies, 2025)
Study region: The Yellow River Basin (YRB) in China. Study focus: This research constructs and evaluates future flood-inundated urban land, population exposure, and GDP exposure in the YRB under various SSP-RCP scenarios. It also discusses the contributions of different factors to changes in exposure and quantifies the future flood control efficiency of flood protection measures. New hydrological insights for the region: We find that provinces in the lower YRB have a higher proportion of flood-inundated urban land. By the end of the 21st century, the proportion of flood-inundated urban land of the cities in lower YRB is expected to increase. Meanwhile, the average population exposure in the YRB under different SSP scenarios will decrease by 6.22–47.23 %, while GDP exposure will increase by 68–72 % across all SSP scenarios. Compared to climate change, socio-economic development is the primary factor influencing flood exposure. Considering flood protection measures, the lower YRB exhibit higher flood control efficiency, while middle and upper YRB still face high exposure due to insufficient effectiveness of protection measures. Protective efficiency of existing flood control measures will further decline with climate change: by the end of the 21st century, only 25 % of cities in the YRB will effectively reduce population exposure, and 35 % will mitigate GDP exposure.